Analysis of the Al-Miftah Curriculum and Learning Methods in Improving Literacy in Reading the Yellow Book and the Quality of Islamic Boarding Schools for Elementary Level Students - Aziz, Lalu Abdul; Fauzan, Ahmad; Haryadi, Herjan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Pesantren as one of the formal education platforms that has a big share in advancing a higher quality life. The quality of pesantren lies in the curriculum and learning methodology used. Al-Miftah learning methodology as a new method used by Ponpes Nujumul Huda in making it easier for students at the basic level to understand how to read the yellow book. The purpose of this study is to analyze the curriculum and learning methodology of Al-Miftah in improving the literacy of reading the yellow book and the quality of elementary level students. The method used is qualitative methodology with the type of field research (Filed Reseach). collection techniques using observation, interviews and documentation. Data analysis used is data reduction, data display and conclusion drawing. Data validity uses researcher diligence, extended observation and triangulation. The results of the research in the process of yellow book literacy starting from the basic level of junior high school, starting from memorizing nazom with a method that is very easy to understand and more detailed material accompanied by drums. The packaging of the learning process is in accordance with the developmental period and the psychological state of the students. Public testing activities once for 3 or 4 months. the supporting factor is the full support of the pesantren leadership, teachers and commitment in cooperation. And the inhibiting factor is the inner state of the students.